Implementation of Meaningful Participation in Every Stage of Local Regulation Formation - Muja’hidah; Adiesty S.P. Syamsuddin; Asriyani; Ansar; Asia Hukama Sari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Public participation in forming legislation is necessary in the framework of people’s sovereignty. The existence of a mechanism for channelling public aspirations and views on the draft of a regulation is guaranteed by the Constitution as part of the implementation of the right to be heard, the right to be considered, and the right to be explained. This article aims to define public involvement in each stage of local regulation formation concerning the principle of people’s sovereignty and investigate the mechanisms that enable meaningful public participation at each stage of law and regulation formation. This article employs a normative juridical research method using statutory and conceptual approaches. This article shows that not all stages of local regulation formation can incorporate public participation. This article concluded that among the six stages of local regulation formation, only three stages can be implemented using community participation through citizens’ rights to be heard, the right to be considered, and the right to be explained. The three stages are planning, drafting, and discussion. Currently, there are several ways of public participation regulated in laws and regulations for the law-making process: FGD and public hearings. However, in the spirit of popular sovereignty, there are also ways of channelling opinions through petitions and demonstrations.